Evaluasi dan Supervisi Proses Pembelajaran; Sebuah Analisis terhadap Artikel Ratna Puspita Sari Dkk. - Ahmad Syaifuddin; Siswadi Siswadi; Abdor Rohman Wahid (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
Abstract from Ratna Puspita Sari's writing; The aim of this research is to examine the evaluation and supervision of the learning process as an effort to increase teacher professionalism in schools. The method used is a qualitative research method with a type of field research. The research locations in this study were MA Darul Hikmah Jember, MA Fatihul Ulum Al Mahfudz, MAN 1 Jember, and MAN 2 Jember. The findings in this research are that in general the implementation of academic supervision at MA Darul Hikmah Jember, MA Fatihul Ulum Al Mahfudz, MAN 1 Jember, and MAN 2 Jember has gone well. School supervisors have an adequate understanding of academic supervision and can carry out supervisory duties and functions well. Second, there are still limitations in the aspects that are the target of academic supervision by Madrasah supervisors at MA Darul Hikmah Jember, MA Fatihul Ulum Al Mahfudz. Not all aspects of academic supervision are the focus of school supervisors. Meanwhile, at MAN 1 Jember and MAN 2 Jember, all aspects have been implemented by madrasah supervisors. Aspects supervised include learning planning, teaching and learning implementation, class management, and follow-up on learning results. Third, Madrasah Supervisors have developed quite varied academic supervision techniques at MA Darul Hikmah Jember, MA Fatihul Ulum Al Mahfudz, MAN 1 Jember, and MAN 2 Jember. Techniques used include individual supervision, such as class visits, observations, and individual meetings; group supervision, such as teacher meetings/supervision meetings, committees, and group work, as in MGMP. The approaches used in monitoring activities include those of officials, partners and families.